Aetiological Significance of Infectious Stimuli in Kawasaki Disease - Nakamura, Akihiro; Ikeda, Kazuyuki; Hamaoka, Kenji (Frontiers in Pediatrics, 2019)
Abstract Kawasaki disease (KD) is a paediatric vasculitis syndrome that is often involves coronary artery lesions (e.g., coronary artery aneurysms). Although its causal factors and entire pathogenesis remain elusive, the available evidence indicates that the pathogenesis of KD is closely associated with dysregulation of immune responses to various viruses or microbes. In this short review, we address several essential aspects of the aetiology of KD with respect to the immune response to infectious stimuli: 1) the role of viral infections, 2) the role of bacterial infections and the superantigen hypothesis, 3) involvement of innate immune response including pathogens/microbe-associated molecular patterns and complement pathways, and 4) the influence of genetic background on the response to infectious stimuli. Based on the clinical and experimental evidence, we discuss the possibility that a wide range of microbes and viruses could cause KD through common and distinct immune processes.